Strategi Pemasaran UMKM Kyon Pocha Subang - Siti Titta Partini; Mulyani Mulyani; Cindy Marjiatul Hasanah (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
The development of information technology today has encouraged a phenomenon called global culture, one of which is known as Korean wave or the influence of Korean culture which also influences young people in Indonesia. The increasing demand for Korean food has been responded positively by a number of teenagers in Subang Regency by managing the Kyon Pocha UMKM business. This study aims to determine and analyze the marketing strategy implemented by the Kyon Pocha UMKM based on segmentation, targeting, positioning or known as STP, as well as the marketing mix based on the 'seven Ps' or product strategy, pricing, place, promotion, people, physical evidence and process. The research method uses a qualitative descriptive approach with data collection techniques using interviews, observations and literature studies. The results of the study indicate that the marketing mix of the Kyon Pocha Subang UMKM is in accordance with STP and is implemented quite well, but needs to be improved especially in relation to product variants, market expansion, more effective use of social media and physical evidence.